Registry Based Analysis Of Cost-Of-Illness Study Among Stage C Heart Failure Patients At Hospital Queen Elizabeth Ii, Sabah, Malaysia - Tan, Yui Ping (2018)
Numerous cost-of-illness studies of heart failure have been published in developed countries but such knowledge is currently lacking in Malaysia. Such knowledge can assist the healthcare decision makers to identify the cost driver of heart failure. To fill the gap, the main objective of this study was therefore to estimate the mean annual cost of Stage C heart failure in Hospital Queen Elizabeth II based on the ASIAN-HF registry data. The specific objectives were to validate ASIAN-HF Registry data, to estimate the prevalence of Stage C heart failure and to identify the patient demographic characteristics, clinical history, comorbidities and outcome events among registry patients with Stage C heart failure in Hospital Queen Elizabeth II.